Phishing attacks or COVID-19 and Remote Work Security - Reddy Vaka, Pavan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
The COVID-19 pandemic accelerated the adoption of remote work, which significantly altered the cybersecurity landscape. One of the most common cyber threats that surfaced during this period was phishing attacks, which exploit vulnerabilities associated with remote work setups. Phishing attacks have evolved in sophistication, targeting both employees and organizations, and they have increasingly leveraged the global health crisis to create more convincing attack vectors. This research investigates the relationship between the surge in phishing attacks and the widespread shift to remote work during the COVID-19 pandemic. By analyzing the patterns of phishing attempts, the role of organizational security policies, and individual employee behaviors, the study highlights the increased vulnerability of remote work environments to phishing schemes. The paper also explores security measures that can be implemented to mitigate these risks and proposes a set of recommendations for organizations to improve remote work security posture in a post-pandemic world. Findings indicate that remote work environments have heightened the risk of phishing attacks, suggesting the need for more robust cybersecurity strategies and continuous employee awareness training.